KOMPOSISI ASAM LEMAK PADA DAGING SAPI RANCAH DAN PERANAKAN ONGOLE - Nena Hilmia; Dedi Rahmat; Primiani Edianingsih; Yurleni Faisal (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Local beef is known for its low-fat content/lean meat. The fatty acid profile of beef could affect the meat quality, related to its texture, taste, and nutritional value. This study aims to determine the fatty acid profile of Rancah and Ongole Grade beef. This study used fourteen samples of meat from Rancah cattle 1.5 – 2.5 years, which were extensively reared with forage feed, and nine samples of Ongole Grade beef with forage and concentrate feeding as much as 2.5% dry matter of body weight. A fatty acid profile was analyzed from the longissimus dorsi muscle area, between the 12th and 13th ribs. The fatty acid profiles identified are saturated and unsaturated fatty acids (MUFA and PUFA). The fatty acid analysis used is the Gas Chromatography (GCMS) method. The data were analyzed descriptively and fatty acid composition differences of Rancah and Ongole grade beef were analyzed by T-test. The results showed that the fatty acid composition of Rancah and Ongole grade beef is relatively the same as the beef of other breeds. Saturated fatty acid in Ongole Grade beef is higher than Rancah beef, but the content of unsaturated fatty acids, PUFA/MUFA: SFA ratio in Rancah beef is higher than Ongole Grade.